Impact of environmental method training on the accuracy shoot fixed in basketball - Zerf, Mohammed (The Swedish Journal of Scientific Research, 2015)
Free throw lanes are very often repeated gestures by players in training, as well as double-step. It is indeed a chance to score without opposition, for lot of number points in every game, given after a foul or violation.(Delobel, Karine, QA International Collective, Fourny, Denis, 2000. p266) indicates there average in with 25 per faults committed by team in competition that the statistics they represent a possibility of 35 points per game. As that, we confirm the advantages of the investing in the free throws that are fundamental technical factor, which we must consist in our training player’s basketball. Previously, our study came to shows the impact and the importance of the methods to develop the precision in shooting in basketball. Our aims in this study: Comparing the advantages of our tool fabricant based on the probability surfaces (sin α= the diameter of the balloon/diameter of the hoop) to demonstrate the prospect of initial position in three dimensions (face the haunts (small and large square) of the table, left and right (away from the haunts of the table)). With the status of SHARPE (smaller diameter circles 1975) and SAMIKOP (circles inclined to the horizontal 1976) in the Shooting Fixed on Basketball.
Keywords: Environmental Method; The Accuracy; Shooting Fixed in Basketball